1997
DOI: 10.1021/je970005k
|View full text |Cite
|
Sign up to set email alerts
|

Densities, Molar Volumes, Thermal Expansion Coefficients, and Isothermal Compressibilities of Organic Acids from 293.15 K to 323.15 K and at Pressures up to 25 MPa

Abstract: Densities of seven straight-chain organic acids, including acetic acid, propanoic acid, butanoic acid, pentanoic acid, hexanoic acid, heptanoic acid, and octanoic acid, have been measured by using a vibrating-tube densimeter in the temperature range from 293.15 K to 323.15 K and pressure range from 0.1 MPa to 25.0 MPa. Molar volumes of these organic acids have been obtained from the measured densities and fitted to polynomials as a function of temperature and pressure. Thermal expansion coefficients and isothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 4 publications
2
30
0
Order By: Relevance
“…(A29) to the density and to the isothermal compressibility data reported in 46 and 47 ; and for acetic acid was obtained by fitting Appendix A, Eq. (A1) only to the isothermal density datasets reported in 48 . Table 5: Coefficients for the AspenTech extended Antoine equation 26 , Eq.…”
Section: Modelling Resultsmentioning
confidence: 99%
“…(A29) to the density and to the isothermal compressibility data reported in 46 and 47 ; and for acetic acid was obtained by fitting Appendix A, Eq. (A1) only to the isothermal density datasets reported in 48 . Table 5: Coefficients for the AspenTech extended Antoine equation 26 , Eq.…”
Section: Modelling Resultsmentioning
confidence: 99%
“…The source and purity of chemical compounds used in this study are shown in Table-1 along with experimental measurements of viscosity, density and refractive index, as well as values obtained from other researchers [11][12][13][14][15][16][17][18][19]. All the chemicals and regeants were used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…http://dx.doi.org/10.1016/j.jct.2012.07.019 are given in table 1. The purity of the solvents were checked by comparing the measured density, speed of sound and refractive index value at various temperature with those reported in literature [5,24,26,[29][30][31][32][33][34][35].The literature and experimental density, speed of sound and refractive index value of pure solvents are given in table 2. The maximum difference between the literature and the experimental density, speed of sound and the refractive index is 0.0005 g Á cm À3 , 3.6 m Á s À1 and 0.0024.…”
Section: Methodsmentioning
confidence: 99%
“…Accurate knowledge of the thermodynamic properties of carboxylic acid mixtures are also useful for the development of new correlations and/or predictive models [10,11]. The density, speed of sound and refractive index data on carboxylic acid binary mixtures in literature is limited and most of the work have been done with small chain acids at one temperature 298.15 K [12][13][14][15][16][17][18][19][20][21][22][23][24]. There is no speed of sound binary data for carboxylic acid mixtures.…”
Section: Introductionmentioning
confidence: 99%